Weed control systems for upland rice production - Moody, K. (1974)
Nearly one-quarter of the total rice area of the world is planted to upland rice (10). At least two-thirds of the production in Latin America and West Africa is from upland culture (3, 36). Probably 30-40 percent of the rice in the world is grown following dry soil preparation (23~. Much of the upland rice in West Africa is grown on small farms under shifting cultivation. With this system, the farmer clears the underbrush towards the end of the dry season leaving the large trees of economic value intact (18). Generally the stumps and roots from~ hich the forest regenerates are left in the ground (13). The underbrush is allowed to dry and is then burnt. After the commencement of the rains, the farmer sows his crop of rice which may be mixed with other crop seeds using a hoe with which he scratches the surface soil to cover the seeds (18). Farms rarely exceed 1 hectare in size mainly~ because the farmer is unable to weed a larger area.